Teaching volleyball using exploratory animation software: "Defense positions during the reception of service with 4-2 defense formation and 6 at the front" - Antoniou, P.; Mastrogiannis, I. (International Journal of Computer Science in Sport, 2002)
There are activities in Physical Education where students and teachers face learning and teaching difficulties correspondingly. By hands-on experience at school, we consider that activities that fall into this category are the acquisition of the correct positions of a volleyball team`s players during the reception of the service and the setter`s movement. They are also time-consuming since, ideally, all students should assume the correct positions for all possible initial positions (right before the execution of the service) on the volleyball court. The suggested defense formation at high school and lyceum level is "W" with 6 at the front and two setters (4-2).